2019
DOI: 10.21595/vp.2019.21099
|View full text |Cite
|
Sign up to set email alerts
|

Natural frequency analysis of a functionally graded rotor system using three-dimensional finite element method

Abstract: Three-dimensional Finite Element (FE) analysis has been carried out using ANSYS software to study the natural frequencies of functionally graded (FG) rotor system. Temperature and position-dependent material properties of the FG shaft system are considered to be graded in the radial direction. Power-law with the nonlinear temperature distribution (NLTD) and exponential law with exponential temperature distribution (ETD) have been used to model the material gradation and temperature distribution. Rotor systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…Different analyses have been carried out including the Campbell diagram, stability speed limit and damping ratio. Bose and Sathujoda [ 18 ] performed a natural frequency analysis of a functionally graded rotor system using a three-dimensional finite element model developed using ANSYS (ANSYS 18.0, ANSYS, Canonsburg, PA, USA). Furthermore, Bose and Sathujoda [ 19 ] extended this work and studied the effects of thermal gradients on the vibration characteristics of an FG rotor-bearing system.…”
Section: Introductionmentioning
confidence: 99%
“…Different analyses have been carried out including the Campbell diagram, stability speed limit and damping ratio. Bose and Sathujoda [ 18 ] performed a natural frequency analysis of a functionally graded rotor system using a three-dimensional finite element model developed using ANSYS (ANSYS 18.0, ANSYS, Canonsburg, PA, USA). Furthermore, Bose and Sathujoda [ 19 ] extended this work and studied the effects of thermal gradients on the vibration characteristics of an FG rotor-bearing system.…”
Section: Introductionmentioning
confidence: 99%
“…Few works were detailed on functionally graded rotor-bearing systems in the literature. Bose and Sathujoda [13] performed the free vibration analysis to investigate the natural frequencies of an FG rotor-bearing system using the three-dimensional finite element method. Since the FGMs can withstand high temperatures, the influence of temperature gradient on FG structures and rotating systems must be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the numerical solution of the Reynolds equation and the analytical description of the resulting variables, the model was finally applied to the virtual turbocharger assembled in the multibody system [8]. Bose et al (2019) modelled material-level matching and temperature distribution using NLTD (Nonlinear Temperature Distribution,) and ETD (Exponential Temperature Distribution), and studied two different FG (Functionally Graded) materials, stainless steel-ZrO2 and stainless steel-Al2O3 rotor systems. The results showed that different idempotent coefficients, materials and laws of materials affected the natural frequency of rotor systems [9].…”
Section: Introductionmentioning
confidence: 99%
“…Bose et al (2019) modelled material-level matching and temperature distribution using NLTD (Nonlinear Temperature Distribution,) and ETD (Exponential Temperature Distribution), and studied two different FG (Functionally Graded) materials, stainless steel-ZrO2 and stainless steel-Al2O3 rotor systems. The results showed that different idempotent coefficients, materials and laws of materials affected the natural frequency of rotor systems [9]. Bouzidi et al (2020) analysed the dynamic characteristics of the functional gradient rotor-blade system using the finite element method, modelled the rotor-blade system using the Euler-Bernoulli beam theory, and finally discussed the effect of power-law distribution on the inherent frequency of the rotor-blade system.…”
Section: Introductionmentioning
confidence: 99%